Предмет: Математика,
автор: vikakovalenko274
Время кончается?!!!
Приложения:
Ответы
Автор ответа:
0
Ответ:
(t + 7,7)( t^2 + 16,3t + 66,49)
Пошаговое объяснение:
(t + 8)^3 - (0,3)^3 =
= (t + 8 - 0,3) ((t + 8)^2 + (t + 8)*0,3 + 0,09)
= (t + 7,7)( t^2 + 16t + 64 + 0,3t + 2,4 + 0,09) =
= (t + 7,7)( t^2 + 16,3t + 66,49)
Автор ответа:
0
(t+7,7)(t^2+16,3t+66,49)
Похожие вопросы
Предмет: Английский язык,
автор: LacrymosaLenta
Предмет: Русский язык,
автор: Тинай
Предмет: Русский язык,
автор: ФистАшКо
Предмет: Биология,
автор: Jkay1
Предмет: Математика,
автор: Кристя12344